Perfíl metabólico e mineral de vacas no período peri-parto: qualidade e conformação dos cascos - Fernando Passon Casagrande (2013)
Claw measurements were assessed for conformation, hardness, growth and wear of hoof and the occurrence of foot lesions in thirty crossbred dairy cows at 30 days antepartum, delivery, and at 30, 60 and 90 days of lactation, changes in the profiles energetic and mineral at 5 and 10 days postpartum and their correlation with the measurements of the claw in the first three months of lactation. Observed increase in the claw angle and heel depth and decrease of dorsal wall length between the 30 days pre-partum and 90 days of lactation. The hardness of the claw decreased at day 30 of lactation the measurements done on the wall and the sole-wall. In the white line and sole the hardness decreased at birth and at 30 days of lactation. The claw growth rate reduced and claw wear increased in the first month of lactation. Were identified correlations between the concentrations of calcium, phosphorus, magnesium and non-esterified fatty acids (NEFA) at postpartum and claw measurements evaluated in the first three months of lactation. Low concentrations of serum calcium were correlated with lower claw growth rate and the lower claw hardness. Low magnesium concentrations were correlated with higher claw wear rate. High NEFA concentrations presented correlation with lower claw hardness.